PENERAPAN ACTIVE LEARNING STRATEGI KONSTRUKTIVISME PADA PEMBELAJARAN ALQUR’AN HADIS DI MADRASAH TSANAWIYAH NEGERI 2 LABUHANBATU - Siti Aisah (ANSIRU PAI : Pengembangan Profesi Guru Pendidikan Agama Islam, 2019)
This study aims to answer the problems posed, namely how:(1) teacherpreparation for the Hadith in applying the constructivism learningstrategies? (2) the application of the steps of the Hadith Al-Qur'an teacherapplies the constructivism learning strategies? (3) the involvement ofstudents in the learning of the Qur'an Hadith using constructnivism? (4)constraints or barriers to the Qur'anic Hadith teacher in applyingconstructivism, andn (5) the effectiveness and learning outcomes of the Al-Qur'an Hadith and the application of the constructivism learningstrategies?. The subjects of this study were the two Qur'anic Hadithteachers who worked over five years. Data collection techniques arecarried out by observation, interviews, and document studies. The dataanalysis technique uses three stages, data reduction, data display, andconclusion as recommended by Miles and Huberman. The results, First,the teacher has made preparations before conducting teaching activities inthe form of preparation of syllabus and Learning Implementation Plansthat have been previously validated (checked) by the principal. Second, theimplementation of constructivism learning strategis in learning has beencarried out, but from the four steps of the constructivism learningstrategies it has not been fully implemented properly. Third, studentinvolvement in learning tends to be active and the learning conditions arepleasant. Fourth, the obstacles or obstacles encountered by the teacherrelate to the circumstances and completeness of learning resources andmedia. Fifth, the effectiveness and student learning outcomes increasewhich can be seen from the acquisition of their mastery learning value.